1964
DOI: 10.1002/pol.1964.100020128
|View full text |Cite
|
Sign up to set email alerts
|

Cationic polymerization of 3‐methylbutene‐1. I. Polymerizations at moderately low temperatures

Abstract: SynopsisThe cationic polymerization of 3-methylbutene-1 was investigated with the use of aluminum chloride and aluminum bromide initiators in the temperature range of -62 to -102°C. Polymerizations are homogeneous in the presence of pentane, and above -50°C. in methyl chloride. However, the polymer tends to precipitate below -5OOC. in methyl chloride. The molecular weight of poly-3-methylbutene-1 increases with decreasing temperatures a t the same conversion level. Significantly, the molecular weights increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1966
1966
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…[24][25][26][27][28][29][30] Instead of yielding the expected product of olefin polymerization (polyethylene with an isopropyl group on every other carbon), the polymerization proceeded via a 2,3-type hydride shift to form a tertiary carbocation during each propagation step, yielding a gemdimethyl on every third carbon. They reported that if the Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[24][25][26][27][28][29][30] Instead of yielding the expected product of olefin polymerization (polyethylene with an isopropyl group on every other carbon), the polymerization proceeded via a 2,3-type hydride shift to form a tertiary carbocation during each propagation step, yielding a gemdimethyl on every third carbon. They reported that if the Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…polymerization was conducted above À120 8C, high conversions could be achieved, but the polymer formed was completely amorphous and rubbery. [27] This was most likely due to the presence of non-hydrogen-shifted repeat units in the polymer, although the NMR techniques of the day were not resolved enough to determine the specific content of the two repeat units in the polymer samples. [30] However, when the polymerization was conducted at À130 8C, the polymer was exclusively hydrogen shifted and consequently was 25-30% crystalline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activated complexes arc probably also involved in chain transfer [eqs. (7) and (9)] and termination [eqs. ( 8 ) arid (lo)] reactions which do not affect, polymer structure but do influence molecular weights and conversions.…”
Section: Proposed Polymerization Mechanismmentioning
confidence: 99%
“…Thus, a t steady state, the degree of polymerization should be unaffected by monomer concentration. Similarly, while diffusion should control the rates of reactions ( 2 ) and (3), the relative rates of reactions (5) and (6) to reactions (7), (S), (9), and (10) should be independent of diffusion.…”
mentioning
confidence: 99%